Highly stable laser-scribed flexible planar microsupercapacitor using mushroom derived carbon electrodes - Yadav, Poonam; Basu, Aniruddha; Suryawanshi, Anil; Game, Onkar S.; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
A report is presented on the fabrication of all solid-state interdigitated flexible microsupercapacitor using ultrafast and highly scalable laser scribing technique, using highly mesoporous carbon synthesized from biomass (mushroom) with hydrothermal preprocessing. The specific protocol used for carbon synthesis renders some unique property features to the material (surface area of 2604 m(2) g(-1) with hierarchical pore size distribution) in the context of supercapacitor electrode application. A polyvinyl alcohol (PVA)-H2SO4 gel electrolyte is used for electrochemical measurements. The microsupercapacitor shows high cyclic stability up to 15000 cycles. Moreover it shows nearly 90% stability after 1000 bending cycles at 60 degrees angle. It also retains its performance even under 120 degrees bending condition. This work represents a facile and fast technique for microscaled device fabrication that can be easily commercialized. Moreover, the mushroom-derived carbon used to make the electrodes holds great promise in context of the stability and flexibility of flexible supercapacitors.